The Resource-based View and SME Internationalisation: An Emerging Economy Perspective - Rūta Kazlauskaitė; Erkko Autio; Modestas Gelbūda; Tadas Šarapovas (Entrepreneurial Business and Economics Review, 2015)
Objective: The aim of the paper is to advance the development of theory in the field of international business by seeking to understand to what extent the resource-based view (RBV), built on the experience and evidence from advanced economies, helps understand the internationalisation process of emerging economy SMEs.